The Effect of Social Media on Corporate Innovation: Evidence from Seeking Alpha Coverage - He, Qiyang; Leung, Henry; Qiu, Buhui; Zhou, Zhou (Management Science, 2025)
Seeking Alpha (SA) is the most popular crowdsourced social media platform specializing in the financial analysis of U.S. firms, and it attracts over 17 million visitors per month. We find that firm coverage initiation on SA significantly promotes corporate innovation activities. SA coverage promotes corporate innovation by disseminating innovation-related information about the covered firm to external investors, thereby alleviating the firm’s financial constraints. Moreover, firms with higher information asymmetry, firms facing greater product market competition, and firms having lower levels of managerial short-termism reveal a greater increase in innovation outcomes following SA coverage initiation. Taken together, our findings suggest that third party-generated information on specialized social media mitigates the information asymmetry between firms and investors on corporate innovation activities and encourages corporate innovation. This paper was accepted by Bo Becker, finance. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2023.00995 .